Android Battery Saver System - Silvester, Eastwood Arthur Maclane; Marjudi, Suziyanti (Applied Information Technology And Computer Science, 2023)
Android Battery Saver System is an application that helps to conserve the battery life of a device. Most smartphones these days have included a built-in battery-saver feature which helps limit their battery consumption. Unfortunately, it is not included in older smartphones or older version of android. With over 83.32% of the world’s population having smartphones today, most people are having a hard time maintaining their smartphones’ battery life. Therefore, an application which is Android Battery Saver System is proposed. The system is designed using object- oriented approach, and the model used is the agile model as this model is the best for application development. In addition, the application is developed using Android Studio and Firebase to store data in database. Finally, it is expected that Android Battery Saver System can be used optimally and benefit android smartphone users.